PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM PENGEMBANGAN KARIR KARYAWAN PERUMDA BPR BANK GRESIK - Haninah Hanim; Heru Baskoro (Trending: Jurnal Manajemen dan Ekonomi, 2023)
Career development, is a planning process that allows employees to identify career goals and paths that lead to these goals. This study aims to determine the role of Perumda BPR Bank Gresik in the career development of its employees. The research method used is qualitative research using a case study model, which is an in-depth and detailed research for an area that has a certain background, one research subject, one document or one event. The results of this study indicate that to assist the career development of its employees, human resource management Perumda BPR Bank Gresik has conducted continuous training and there is an evaluation in the process so that training can run optimally in employee career development. Including legal training, banking training and others that have certification for employee development. In addition, Perumda BPR Bank Gresik also helps employee career development through promotions starting from the organisational structure that has been agreed by the board of directors. However, Perumda BPR Bank Gresik does not carry out mutations for employees because the reason is that the placement of employees who are already suitable if overhauled will damage employee performance.